2022
DOI: 10.3390/genes13030514
|View full text |Cite
|
Sign up to set email alerts
|

KMT2A: Umbrella Gene for Multiple Diseases

Abstract: KMT2A (Lysine methyltransferase 2A) is a member of the epigenetic machinery, encoding a lysine methyltransferase responsible for the transcriptional activation through lysine 4 of histone 3 (H3K4) methylation. KMT2A has a crucial role in gene expression, thus it is associated to pathological conditions when found mutated. KMT2A germinal mutations are associated to Wiedemann–Steiner syndrome and also in patients with initial clinical diagnosis of several other chromatinopathies (i.e., Coffin–Siris syndromes, Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 103 publications
0
26
0
Order By: Relevance
“…A rare developmental disorder known as Kabuki syndrome (KS) is characterized by postnatal growth restriction, characteristic facial features (such as long palpebral fissures in the lateral third of the lower eyelids, arched and broad eyebrows with the lateral third displaying notches or sparseness, large, prominent, or cupped ears, and short columella with a depressed nasal tip), skeletal anomalies (such as brachymesophalangy, brachydactyly V, spinal column abnormalities, and fifth digit clinodactyly), dermatoglyphic abnormalities (persistent fingertip pads), and mild-to-moderate intellectual disability [ 36 ]. KS is primarily (60%) caused by mutations in KMT2D , or less often in KDM6A [ 36 , 37 ]. Cornelia De Lange syndrome (CdLS) is an archetypical genetic syndrome characterized by ID, distinctive facial features, malformations of the upper limbs, and atypical growth, among numerous other signs and symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…A rare developmental disorder known as Kabuki syndrome (KS) is characterized by postnatal growth restriction, characteristic facial features (such as long palpebral fissures in the lateral third of the lower eyelids, arched and broad eyebrows with the lateral third displaying notches or sparseness, large, prominent, or cupped ears, and short columella with a depressed nasal tip), skeletal anomalies (such as brachymesophalangy, brachydactyly V, spinal column abnormalities, and fifth digit clinodactyly), dermatoglyphic abnormalities (persistent fingertip pads), and mild-to-moderate intellectual disability [ 36 ]. KS is primarily (60%) caused by mutations in KMT2D , or less often in KDM6A [ 36 , 37 ]. Cornelia De Lange syndrome (CdLS) is an archetypical genetic syndrome characterized by ID, distinctive facial features, malformations of the upper limbs, and atypical growth, among numerous other signs and symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, horseshoe kidney with/without pyelectasis was never reported in any SDS patient (PubMed and Google Scholar search, June 2022, using horseshoe kidney AND Shwachman-Diamond Syndrome), and is found in approximately 0.25% of the general population; moreover, it is more commonly reported in WDSTS, with six patients showing this malformation [ 40 , 49 , 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Large scale exome sequencing studies identified mutations in MLL1/KMT2A among patients presenting with developmental delay and ID (Deciphering Developmental Disorders Study, 2015;Lelieveld et al, 2016;Trujillano et al, 2017). Clinical genetics studies identified MLL1/KMT2A pathogenic variants in patients diagnosed with either Kabuki syndrome or Rubinstein-Taiby syndrome which are characterized by ID, postnatal growth defects and microcephaly (Sobreira et al, 2017;Castiglioni et al, 2022).…”
Section: Mll1/kmt2a a Central Contributor To The Pathogenesis Of Mult...mentioning
confidence: 99%